The Tomb of Mbah Kalibening: Pilgrimage, Sacred Heritage, and Community Empowerment - Aliza Putri Khairunnisa; Muhammad Noval Rofif (JURNAL ISLAM NUSANTARA, 2026)
This study aims to analyze the meaning, procedures, impacts, and purposes of a sacred tomb as a religious and cultural site. Sacred tombs function as spaces of devotion, memory, and community identity, yet their broader social significance is often overlooked or reduced to tourism. This research employed a qualitative descriptive approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed using reduction, display, and conclusion drawing. Findings reveal that the tomb’s historical narratives connect the figure of a revered scholar with sacred-water symbolism, reinforcing spiritual authority and cultural memory. Pilgrimage procedures integrate bathing, ablution, prayer, and reflection, demonstrating how physical and spiritual preparation are intertwined. The site generates economic opportunities for residents and strengthens social cohesion through collective participation in rituals and site maintenance. Culturally, it preserves ancestral memory and transmits local wisdom, while spiritually encouraging reflection on mortality, blessing, and moral conduct. The study contributes to religious tourism and heritage research by conceptualizing sacred tombs as multi-dimensional institutions. Participatory and culturally sensitive management is recommended to sustain these benefits.